Reinstatement of Leuctra biellensis Festa, 1942 (Plecoptera, Leuctridae) - Gilles Vinçon; Louis Boumans; Jean-Luc Gattolliat (Alpine Entomology, 2018)
Both molecular and morphologic characters support the reinstatement of Leuctra biellensis Festa, 1942 as a valid species distinct from Leuctra nigra (Olivier, 1811). Genetic distances between L. biellensis and the different populations of L. nigra are around 9%, while intraspecific distances among L. nigra haploclades are less than 1%. Morphologically, the two species can be separated in male adult specimens by the shape of the two teeth on tergite VIII, by the lateral edges of tergites and by the distal expansion of the paraprocts. Leuctra biellensis occurs on the southern slope of the Alps in Italy and Switzerland (Ticino and Graubünden), while L. nigra has a wide distribution in Central and Northern Europe. As the type material of L. biellensis was lost, and to avoid future confusion between the two species, we designate as neotype a male imago collected at the type locality.